PERAN ILMU-ILMU BUDAYA DALAM STRATEGI PENGEMBANGAN BUDAYA NASIONAL - . Herwandi (Humaniora, 2007)
It seems that cultural science has been marginalized in Indonesian development. This marginalization might be the result of the continuity of the history of science. The cultural science is considered worthless; meanwhile the natural science with its divisions are regarded as the proper science as they may be used to face the problems encountered in Indonesia. The cultural science should possess the central roles in giving the touch of humanity to every aspect of life in this nation.